Simple techniques to enhance the governance of a family business - Enrique Antonio Yacuzzi (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2013)
The use of simple governance techniques at a hypothetical family business (called ABC) will be beneficial. Good governance leads to a better relationship among stakeholders, increases the effectiveness of family institutions and board work and activates unknown potential at the firm through better principles and practices. Tools proposed are: (1) A new and flexible family business governance indicator, developed for this paper; (2) Hoshin management; and (3) Effective meeting technology. The three techniques interact in a systemic mode. The indicator allows measurement of how family business governance evolves through time in a company and facilitates comparison between different companies' governance. Most importantly, it is a checklist and roadmap to better governance. Hoshin management is a generic planning method that can be used to build a governance improvement plan. Effective meetings facilitate planning and control and in this sense they are a tool for governance improvement. This paper is mainly based on the following sources: IFC (2008), Yacuzzi (2005 b, 2007, 2008, 2012), Yacuzzi et al. (2011), Naiberger & Yacuzzi (2009). To an important extent, the paper's organization is based on Yacuzzi (2012).
Keywords: 330; Familienunternehmen; Corporate Governance